Association between dietary patterns and serum adiponectin: a cross-sectional study in a Japanese population. (17th February 2018) - Bahari, Tirani; Uemura, Hirokazu; Katsuura-Kamano, Sakurako; Yamaguchi, Miwa; Nakamoto, Mariko; Miki, Keisuke; Sawachika, Fusakazu; Arisawa, Kokichi
Abstract: The aim of this study was to evaluate the associations between dietary pattern, adiponectin and insulin resistance. The study population consisted of 612 men and women aged 35–69 years old who had participated in the baseline survey of Japan Multi-Institutional Collaborative Cohort (J-MICC) Study in Tokushima Prefecture. Diets and lifestyle related variables were assessed by questionnaires. Multiple regression analyses were used to analyse the relations between dietary patterns and high molecular weight (HMW) adiponectin. For further analysis, path analysis was used to test the hypothesised model of association between dietary pattern, serum adiponectin and insulin resistance. The result showed that higher score of bread and dairy pattern was directly associated with increased serum level of adiponectin in women, which was inversely related to homeostasis model assessment of insulin resistance (HOMA-IR). In conclusion, higher consumption of bread and dairy products, and low intake of rice may be associated with increased serum adiponectin in women.